Light-induced LC director freezing on a chalcogenide surface. Issue 2 (26th January 2016) - Sheremet, N.; Golub, P.; Kurioz, Y.; Trunov, M.; Reznikov, Y.
ABSTRACT: First observations of permanent light-induced director patterning in a transparent liquid crystal (LC) are reported. The patterning was observed in an LC cell with one of the substrates covered with a chalcogenide film. Concentric director ring pattern appears following the irradiation of the chalcogenide surface through the LC layer by a Gaussian beam. The experimental results are explained in terms of the heat transfer from the chalcogenide film to the LC after the light absorption by the chalcogenide film. Heating the LC changes its birefringence according to the spatial intensity distribution of the Gaussian beam. This in turn leads to the spatially oscillating changes of the polarisation state of light in the plane of the chalcogenide film. The oscillating changes of the light polarisation result in producing the light-induced easy orientation axis and the oscillating changes of the anchoring energy. It causes the spatial modulation of the director on the chalcogenide surface and the formation of the concentric ring twist structures in the cell. Graphical Abstract: